Governing molecules : the discursive politics of genetic engineering in Europe and the United States - Gottweis, Herbert, 1958- (Inside technology., 1998)
Scientists, investors, policymakers, the media, and the general public have all displayed continuing interest in the commercial promise and the potential dangers of genetic engineering. In this book, Herbert Gottweis explains how genetic engineering became so controversial - a technology that some seek to promote by any means and others want to block entirely. Beginning with a clear exposition of poststructuralist theory and of its implications for research methodology, Gottweis takes a novel approach to political analysis, emphasizing the role of narratives in the development of policy.